Evaluation of the effectiveness of an intervention strategy in a control simulation experiment through comparison with model predictive control - R. Nagai; Y. Bai; M. Ogura; M. Ogura; S. Kotsuki; S. Kotsuki; N. Wakamiya (Nonlinear Processes in Geophysics)
Climate change intensifies weather-related disasters, necessitating novel mitigation strategies beyond conventional weather prediction methods. The control simulation experiment (CSE) framework proposes altering weather systems through small perturbations, but its effectiveness relative to other control methods remains uncertain. This study evaluates CSE's efficacy against model predictive control (MPC), a well-established method in control engineering. We specifically develop an MPC algorithm tailored for the Lorenz-63 model, incorporating temporal deep unfolding to address challenges in controlling chaotic systems. Simulations show that MPC achieves higher success rates with less control effort under certain conditions, particularly with shorter prediction horizons. This work bridges control theory and atmospheric science, advancing the understanding of atmospheric controllability and informing future research efforts to mitigate extreme weather events.